2013
DOI: 10.1111/cobi.12124
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Assessing the Prevalence and Drivers of Illegal Bushmeat Hunting in the Serengeti

Abstract: Assessing anthropogenic effects on biological diversity, identifying drivers of human behavior, and motivating behavioral change are at the core of effective conservation. Yet knowledge of people’s behaviors is often limited because the true extent of natural resource exploitation is difficult to ascertain, particularly if it is illegal. To obtain estimates of rule-breaking behavior, a technique has been developed with which to ask sensitive questions. We used this technique, unmatched-count technique (UCT), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 40 publications
4
108
0
Order By: Relevance
“…Additionally, the respondents had generally similar views about the current and future status of the Serengeti but disagreed about how to address issues of conservation concern and were more uncertain about the effectiveness and actual outcomes of management interventions. Patterns found in fisheries can inform the design of governance structures; De Nooy (2013) found that centralized systems, such as found in the Serengeti, have more disagreement overall, and especially within stakeholder groups, whereas comanagement systems have more disagreement between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the respondents had generally similar views about the current and future status of the Serengeti but disagreed about how to address issues of conservation concern and were more uncertain about the effectiveness and actual outcomes of management interventions. Patterns found in fisheries can inform the design of governance structures; De Nooy (2013) found that centralized systems, such as found in the Serengeti, have more disagreement overall, and especially within stakeholder groups, whereas comanagement systems have more disagreement between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Only rarely, researchers will be able to follow hunters or openly record their bags as Coad et al (2010) did in Gabon. Usually, either (i) direct interview techniques, (ii) arrest records or (iii) dietary recall surveys are used (Loibooki et al, 2002;Knapp et al, 2010), and, more recently, also indirect interview approaches (Razafimanahaka et al, 2012;Nuno et al, 2013). Direct interviews with rural residents, asking openly about their involvement in hunting, require participants to explicitly admit to an essentially illegal (albeit possibly widespread and locally accepted) activity.…”
Section: Approachmentioning
confidence: 99%
“…And estimates of household bushmeat consumption from dietary recall surveys (e.g., Foerster et al, 2011;Brashares et al, 2011) have been found a reliable proxy for overall hunting levels (Knapp et al, 2010), but do not per se distinguish between meat bought, and meat hunted by household members. Indirect interview techniques, in turn, such as the Unmatched-Count-Technique require large sample sizes to allow the probabilistic computation of the prevalence of hunting (Nuno et al, 2013) and are thus very data-hungry.…”
Section: Approachmentioning
confidence: 99%
See 2 more Smart Citations